2011
DOI: 10.1111/j.1464-410x.2010.10083.x
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient department repair of urethrocutaneous fistulae using n‐butyl‐cyanoacrylate (NBCA): a single‐centre experience

Abstract: edges of the fistula in patients in group B before the application of the glue. RESULTS• Four patients in group A and three patients in group B had definitive fistula repair (seven of 13), and six of the 13 had fistula recurrence.• Fistulae of ≤ 2 mm were more easily repaired than fistulae of > 2 mm (five of seven vs two of six).• Fistulae that tended to recover were those that responded to the first applications. CONCLUSIONS• In this experience the use of NBCA as a minimally invasive treatment for fistula rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…Use of staplers instead of synthetic adhesives decreases treatment costs considerably with acceptable side effects. [49] Applications in Pediatric Urology Prestipino et al [50] , used CA adhesives for hypospadias surgery, and indicated that they could be used as an alternative to suturing with excellent outcomes in that they form extra film layers, and demonstrate strong tissue bonding capabilities. Adhesives form impermeable watertight barriers for body fluids as urine and blood.…”
Section: Priapismmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of staplers instead of synthetic adhesives decreases treatment costs considerably with acceptable side effects. [49] Applications in Pediatric Urology Prestipino et al [50] , used CA adhesives for hypospadias surgery, and indicated that they could be used as an alternative to suturing with excellent outcomes in that they form extra film layers, and demonstrate strong tissue bonding capabilities. Adhesives form impermeable watertight barriers for body fluids as urine and blood.…”
Section: Priapismmentioning
confidence: 99%
“…Their applications include closure of surgical incision, circumcision, and closure of urethrocutaneous fistulas developed following hypospadias surgery. [50] Cyanoacrylates are favourable alternatives for closure of post-circumcision wounds relative to conventional techniques. In addition to their easy applicability, they considerably shorten operative times, and duration of postoperative pain, ensure eventless safe healing, and provide better cosmetic results.…”
Section: Priapismmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Prestipino and his colleagues[8] used CA in four patients with urethrocutanouse fistula, and three had definitive fistula healing. They concluded that fistulae of ≤ 2 mm tended to recover better.…”
Section: Discussionmentioning
confidence: 99%
“…If no perforation is detected, after careful control of the hemostasis, the trocar is removed. The wound is then closed meticulously with an absorbable interrupted suture and skin suture is performed using cyanoacrylate glue [5,6].…”
Section: Methodsmentioning
confidence: 99%